The Improvement of Dry Eye Symptoms after Pinguecula Excision and Conjunctival Autograft with Fibrin Glue - Jinho Jeong; Gabriel M. Rand; Taejung Kwon; Ji-Won Kwon (Journal of Ophthalmology)
Purpose. To evaluate the association between pinguecula excision and subsequent improvement in dry eye syndrome. Methods. We included 30 consecutive patients with primary nasal pinguecula and dry eye symptoms undergoing ocular surgery for the first time. Criteria for pinguecula excision surgery were nasal location, yellowish color, and protrusion of conjunctiva at least 2 times thicker than adjacent normal conjunctiva as measured by anterior segment optical coherence tomography. Our primary outcomes were 3-month postoperative changes in tear film breakup time (TBUT), Schirmer test, and a dry eye symptom score. Results. 30 eyes from 30 different patients (12 men and 18 women) underwent pinguecula excision and conjunctival autografting using fibrin glue. The mean age was 42.5 ± 8.35 (range 28–63) years. The preoperative protrusion ratio of pinguecula was 2.33 ± 0.28 (range 2.00–2.90). Mean preoperative TBUT, Schirmer test, and dry eye symptom scores were 5.10 ± 1.27 seconds, 6.07 ± 2.27 mm, and 2.80 ± 0.76 points. Mean postoperative 3-month TBUT, Schirmer test, and dry eye symptom scores were 7.80 ± 1.13 seconds, 7.27 ± 2.02 mm, and 0.30 ± 0.47 points, respectively. The median pre- and postoperative changes were found to be statistically significant by Wilcoxon signed-rank tests for TBUT, Schirmer test score, and dry eye symptom score. Conclusion. Surgical excision of pinguecula and conjunctival autograft using fibrin glue is an effective and safe method to improve symptoms of dry eye syndrome.